Implementasi Model Asesmen Kurikulum Merdeka pada Teks Prosedur Kelas VII SMP Negeri 1 Bulango Timur - Salilama, Rahmatia; Supriyadi, Supriyadi; Muslimin, Muslimin; Masie, Sitti Rachmi; Agustin, Puspita Dian (Reduplikasi: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2025)
This study aims to describe the implementation of diagnostic, formative, and summative assessment models in teaching procedural texts to seventh-grade students at SMP Negeri 1 Bulango Timur. The research employed a qualitative descriptive method with data collected through observation, interviews, and documentation. The results revealed that diagnostic assessments were applied to map students’ initial abilities, thereby guiding instructional strategies. Formative assessments were carried out through practice, group discussions, and exercises to improve learning processes. Summative assessments were conducted at the end of lessons using written and oral tests, as well as reflections, to ensure the achievement of learning outcomes. Overall, teachers successfully implemented assessment within the emancipated curriculum framework, although challenges remain regarding limited infrastructure and teachers’ mastery of information technology.